The Application of Murabahah Contract in Credit-Based Sale and Purchase: Implications for Consumer Protection - Siti Ropiah (Department of Islamic Banking, 2025)
Purpose – This research aims to understand the application of Murabahah contracts in credit-based buying and selling in Islam and its implications for consumer protection. Methodology – This study uses a normative approach to understand the legal basis of murabahah. In addition, a study was conducted on the regulations governing Islamic financial institutions, to see how murabah contracts are applied in credit transactions. Findings – The findings of the study show that although this contract is in principle in accordance with sharia, there are several challenges in its implementation, such as information transparency, risk management, and the fulfillment of consumer rights. The legal implications of these findings include the need for increased supervision, customer education, and regulatory updates to ensure consumer protection. Implications – The results of the study provide recommendations to strengthen the Islamic banking system through increasing accountability in the implementation of murabahah contracts to create a fair relationship between banks and customers and support sharia-based economic growth. Originality – This study conducts a comprehensive study related to contract regulations and Murabahah contract practices, and especially its implications for consumer protection.